Ulcerative Colitis in Hematological Malignancies: Paraneoplastic Manifestation or Coincidental Bystander? - Gregorios Christodoulidis; Konstantinos Perivoliotis; Anastasios Manolakis; Alexandros Diamantis; Apostolos Koffas; Dimitrios Magouliotis; Vasiliki Pappi; Dimitrios Zacharoulis (Case Reports in Gastrointestinal Medicine)
Evidence of coexistence of diverse hematological malignancies—lymphoma, leukemia, multiple myeloma, and myelodysplastic syndromes—and either ulcerative colitis or Crohn’s disease can be found in the literature. However, a more “systemic” effort to reach further and examine the potential of either one as paraneoplastic manifestation has not been performed. Based on these, three cases of ulcerative colitis manifesting before, simultaneously, and after the onset of different hematological malignancies are presented and critically evaluated.